Low-resistance ultrasonic laser film and preparation method thereof

By using double-sided coating structure and specific developing layer materials on ultrasonic laser film, the problem of difficulty in distinguishing between single-layer coating and insufficient hiding power is solved, and the self-service printing and low resistance effect of double-sided film is achieved, improving printing Quality and durability.

CN119286032APending Publication Date: 2025-01-10HANGZHOU MEI QING DIGITAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410752440.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing ultrasonic laser film is single-layer coated, and there are problems such as difficulty in distinguishing front and back sides, low utilization rate, insufficient hiding power, and easy reflection of printed images, and it is impossible to achieve self-service printing and low resistance effects.

Method used

Using a double-sided coating structure, hydrophobic spherical powder and wear-resistant agent are used in the developing layer. The combination of micro gear structure and adhesives can reduce coating resistance and improve powder dispersion through wetting agents and leveling agents. and paint leveling, realizing self-service printing of double-sided film.

Benefits of technology

It realizes self-service printing of double-sided ultrasonic laser film, reduces friction resistance and hiding power of printed images, and improves wear resistance and scratch resistance and customer experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure FDA0004888445770000011
    Figure FDA0004888445770000011
Patent Text Reader

Abstract

The invention discloses a low-resistance ultrasonic laser film and a preparation method thereof.The low-resistance ultrasonic laser film comprises a base layer and developing layers coated on the front face and the back face of the base layer, and raw materials of the developing layers comprise, by weight, 10-30 parts of adhesive; 2 to 10 parts of a tackifier; 0.2 to 2 parts of hydrophobic spherical micro powder; 0.1-1 part of a wear-resistant agent; 2-10 parts of a developer; 0.3-2 parts of a wetting agent; and 0.2-1 part of a leveling agent. According to the low-resistance ultrasonic laser film disclosed by the invention, the affinity between powder particles and the developing layer is weakened by the hydrophobic spherical powder added in the developing layer, and the powder particles exist on the surface of the developing layer in a suspended embedded form, so that the motion resistance of the hydrophobic spherical powder particles is reduced, and sliding between the films is realized; therefore, frictional resistance between the films is reduced, and self-service printing of the double-sided ultrasonic laser films is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser films, and in particular to a low-resistance ultrasonic laser film and a preparation method thereof. Background Art

[0002] Early traditional films were non-digital. Like ordinary films, films needed to be imaged in a darkroom after the negative was reversed and the developer and fixer interacted with each other. This is what we call imaging, which is what we call silver halide film, also known as "wet film". Imaging technology has entered a new era, and various new diagnostic systems have emerged and applied to anatomy and diagnosis of diseases. Especially nuclear medicine and medical ultrasound technology. They broke the limitations of previous imaging and provided a new means of non-invasively displaying diseases. With the advent of X-ray computer tomography equipment in the early 1970s and the popularization of digital technology in recent years, medical image output and diagnosis methods have undergone revolutionary changes. Medical imaging technology has taken on a new look, and a new type of digital imaging film that does not require traditional developer and fixer to work, dry film, has also appeared.

[0003] Dry film is the name relative to "wet film", and it is named because it does not need to be developed and fixed in a darkroom. Because its imaging process does not require film washing, it saves a lot of manpower, material resources and space: there is no chemical waste, that is, no waste developer and fixer, which reduces pollution to the environment and saves resources. Moreover, the film can be replaced in a bright room: it is easy to manage and maintain. The structure of dry film is generally composed of a back layer, a bottom layer, a substrate, a bottom layer, an imaging layer and a protective layer. According to different imaging methods, it can be classified into laser printing dry film, inkjet printing dry film and thermal printing dry film. Among them, laser printing film has the advantages of good printing image quality, fast printing speed, image is not easy to fade, long storage time, and convenient processing. It is a very fast image output method in recent years.

[0004] At present, the laser films used in ultrasound are all single-layer coated, which can achieve low-resistance printing and meet the needs of self-service printing. However, due to single-sided coating, there are many disadvantages: First, there are front and back sides, which need to be carefully distinguished when printing, which reduces the convenience of use and customer experience; second, it can only be printed on one side, the utilization rate is not high, which is not conducive to saving and environmental protection; third, single-sided coating has low covering power, and the printed image is very easy to be reflected on the back or other images are very easy to be displayed through the film, which reduces the distinguishability and is not conducive to film reading. Based on the above shortcomings, double-sided coated ultrasound laser films have also been launched on the market, but none of them can achieve self-service printing, that is, they cannot achieve the low resistance effect of single-sided coating. Summary of the invention

[0005] The purpose of the present invention is to provide a low-resistance double-sided coated ultrasonic laser film to achieve self-service printing of double-sided ultrasonic laser film.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides a low-resistance ultrasonic laser film, comprising a base layer and a developing layer coated on both sides of the base layer, wherein the raw materials of the developing layer include, by weight:

[0007]

[0008] Optionally, the raw materials of the developing layer include, in parts by weight:

[0009]

[0010] Optionally, the hydrophobic spherical micropowder is selected from one or more of silicone elastic micropowder, polymethyl methacrylate microsphere powder, modified polytetrafluoroethylene microsphere powder, modified synthetic wax microsphere powder, and modified silica spherical powder.

[0011] Hydrophobic spherical micropowder is used to change the microstructure of the developing layer surface, realize the microscopic movable gear structure, and reduce the resistance between the coatings. Hydrophobic spherical micropowder improves the weather resistance and anti-stickiness of laser film, and has a better feel.

[0012] Optionally, the hydrophobic spherical micropowder is selected from hydrophobic silicone elastic micropowder of 8-12 microns and modified polymethyl methacrylate microsphere powder of 14-18 microns. The particle size difference of hydrophobic spherical micropowder particles of different particle sizes is used to form a surface microscopic gradient and movable structure, so that after the coatings are superimposed on each other, gear-shaped coupling is achieved and the rotation effect is achieved, thereby reducing the resistance between the films.

[0013] Optionally, the adhesive is selected from one or more of ethylene-vinyl acetate copolymer emulsion, polyurethane emulsion, carbonyl styrene butadiene latex, and acrylic emulsion.

[0014] Adhesives are mainly used for coating film formation and bonding.

[0015] Optionally, the tackifier is selected from one or more of rosin resin emulsion, polyvinyl alcohol resin, and polyvinyl pyrrolidone.

[0016] Tackifiers are used to enhance the cohesiveness of the developer and improve the adhesion of the toner.

[0017] Optionally, the wear-resistant agent is selected from one or more of Brazilian wax emulsion, paraffin emulsion, oxidized polyethylene wax powder, water-based polytetrafluoroethylene wax, and silicone emulsion.

[0018] Wear-resistant agents are used to improve the wear and scratch resistance of coatings and to modify the surface of developers.

[0019] Optionally, the anti-wear agent is selected from oxidized polyethylene wax powder with a particle size of 4-8 microns.

[0020] Optionally, the developer is selected from one or more of silicon dioxide, kaolin, talc, calcium carbonate, aluminum oxide, and aluminum silicate.

[0021] The developer provides a bonding and adsorption site for the toner to develop.

[0022] The technology of using abrasion resistant agents to wrap the developer improves the wear and scratch resistance of the coating, while blocking the direct contact between the developer and the hydrophobic spherical micropowder particles, thereby reducing the movement resistance of the hydrophobic spherical micropowder particles.

[0023] Preferably, the developer has a specific surface area of ​​150-250m 2 / g, silica with a particle size of 2-6μm.

[0024] Optionally, the dispersant is a nonionic surfactant selected from one or more of alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, and ethylene oxide adduct of polypropylene glycol. The dispersant is used to disperse the powder in the coating.

[0025] Optionally, the wetting agent is selected from one or more of polyols and silicones. The wetting agent is used to wet the hydrophobic powder particles, reduce the surface tension of the hydrophobic powder, and improve the dispersibility of the hydrophobic powder in the developing layer.

[0026] Optionally, the leveling agent is selected from one or more of acrylic polymers, polyurethanes, and silicones.

[0027] Optionally, the leveling agent is organic silicon, selected from one or more of silicone oil, polydimethylsiloxane, polyether modified organic siloxane, and alkyl modified organic siloxane. The leveling agent is used to improve the leveling property of the developing coating.

[0028] The present invention also provides a method for preparing a low-resistance ultrasonic laser film, comprising the following steps:

[0029] S1: Mix the wetting agent, dispersant, anti-wear agent, developer and dispersion liquid evenly, disperse at high speed for 40-80 minutes, and grind at high speed for 30-60 minutes;

[0030] S2: mixing the mixed solution obtained in step S1 with the adhesive and the tackifier, and dispersing at high speed for 45-80 minutes;

[0031] S3: mixing the mixed solution obtained in step S2 with the hydrophobic spherical micropowder, and dispersing at high speed for 45-80 minutes;

[0032] S4: mixing the mixed solution obtained in step S3 with a leveling agent, dispersing at high speed for 20-40 minutes, and defoaming at low speed to obtain a developing layer coating;

[0033] S5: evenly coating the obtained developing layer coating on both sides of the base layer, and controlling the coating amount to 6-12 g / m2;

[0034] S6: Dry the film obtained in S5 at a temperature of 60-110°C to remove the dispersion liquid, thereby obtaining the low-resistance ultrasonic laser film as described above.

[0035] Optionally, in step S1, the ratio of the added mass of the dispersion to the added amount of the developer is 18-22:1, and the dispersion is water.

[0036] The low-resistance ultrasonic laser film disclosed in the present invention has a hydrophobic spherical powder added to the developing layer, which weakens the affinity between the powder particles and the developing layer, and exists on the surface of the developing layer in a suspended embedded form, thereby reducing the movement resistance of the hydrophobic spherical powder particles, achieving sliding between films, thereby reducing the friction resistance between films, and realizing self-service printing of double-sided ultrasonic laser films. DETAILED DESCRIPTION

[0037] The contents of the present application are described in more detail below through examples, but the following examples are only used to illustrate the contents of the present invention rather than to limit them. Therefore, any changes within the meaning and scope equivalent to the claims of the present invention should be deemed to be included in the scope of the claims.

[0038] The reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.

[0039] Example 1

[0040] Preparation of low resistance ultrasonic laser film:

[0041] Step S1: 0.5 g of silicone wetting agent (Keying KYC-648), 0.35 g of non-ionic polymer dispersant (Lubrizol 27000), 0.3 g of oxidized polyethylene wax wear agent (BASF AF30) with a particle size of 4-8 microns, and a specific surface area of ​​200 m 2 / g, 5g of silica developer (Aerospace SD500) with a particle size of 2-6 microns was mixed evenly with 100g of water, dispersed at high speed for 60min, and then ground at high speed with a basket grinder for 45min;

[0042] S2: Mix the mixed solution obtained in step S1 with 20 g of polyurethane emulsion adhesive (Guangzhou Guanzhi PU2944) and 4 g of polyvinyl alcohol resin tackifier (PVA199), and disperse at high speed for 60 min;

[0043] S3: The mixed solution obtained in step S2 is mixed with 0.53 g of hydrophobic spherical micropowder (including 0.5 g of 6902 hydrophobic organic elastic micropowder with a particle size of 8-12 μm produced by Shanghe Chemical and 0.03 g of EXM-20 modified polymethyl methacrylate micropowder with a particle size of 14-18 μm produced by Sekisui, Japan), and dispersed at high speed for 60 min;

[0044] S4: mixing the mixed solution obtained in step S3 with 0.2 g of an alkyl-modified organic siloxane leveling agent (DiGao 450), dispersing at high speed for 30 min, and defoaming at low speed to obtain a developing layer coating;

[0045] S5: evenly coating the obtained developing layer coating on both sides of the PET base layer, and the coating amount is controlled at 8 g / m2;

[0046] S6: Dry the film obtained in S5 at 80°C to remove the dispersion liquid, thereby obtaining a low-resistance ultrasonic laser film.

[0047] Example 2

[0048] Preparation of low resistance ultrasonic laser film:

[0049] Step S1: 0.5 g of silicone wetting agent (Keying KYC-648), 0.35 g of non-ionic polymer dispersant (Lubrizol 27000), 0.3 g of oxidized polyethylene wax wear agent (LAIBON LB-2000) with a particle size of 5-6 microns and a specific surface area of ​​200 m 2 / g, 5g of silica developer (Aerospace SD-640) with a particle size of 6-8 microns was mixed evenly with 100g of water, dispersed at high speed for 60min, and then ground at high speed with a basket grinder for 45min;

[0050] S2: Mix the mixed solution obtained in step S1 with 20 g of polyurethane emulsion adhesive (Guangzhou Guanzhi PU2944) and 4 g of polyvinyl alcohol resin tackifier (PVA199), and disperse at high speed for 80 min;

[0051] S3: The mixed solution obtained in step S2 is mixed with 0.03 g of hydrophobic spherical micropowder (DY-5070D produced by Deyu) with a particle size of 6-8 μm and EXM-20 type modified polymethyl methacrylate micropowder with a particle size of 14-18 μm produced by Sekisui, Japan, and dispersed at high speed for 60 min;

[0052] S4: mixing the mixed solution obtained in step S3 with 0.2 g of an alkyl-modified organic siloxane leveling agent (DiGao 450), dispersing at high speed for 30 min, and defoaming at low speed to obtain a developing layer coating;

[0053] S5: evenly coating the obtained developing layer coating on both sides of the PET base layer, and the coating amount is controlled at 6 g / m2;

[0054] S6: Dry the film obtained in S5 at 80°C to remove the dispersion liquid, thereby obtaining a low-resistance ultrasonic laser film.

[0055] Comparative Example 1

[0056] Preparation of low ultrasound laser film:

[0057] Step S1: 0.5 g of silicone wetting agent (Keying KYC-648), 0.35 g of non-ionic polymer dispersant (Lubrizol 27000), 0.3 g of oxidized polyethylene wax wear agent (BASF AF30) with a particle size of 4-8 microns, and a specific surface area of ​​200 m 2 / g, 5g of silica developer (Aerospace SD500) with a particle size of 2-6 microns was mixed evenly with 100g of water, dispersed at high speed for 60min, and then ground at high speed with a basket grinder for 45min;

[0058] S2: Mix the mixed solution obtained in step S1 with 20 g of polyurethane emulsion adhesive (Guangzhou Guanzhi PU2944) and 4 g of polyvinyl alcohol resin tackifier (PVA199), and disperse at high speed for 60 min;

[0059] S4: mixing the mixed solution obtained in step S3 with 0.2 g of an alkyl-modified organic siloxane leveling agent (DiGao 450), dispersing at high speed for 30 min, and defoaming at low speed to obtain a developing layer coating;

[0060] S5: evenly coating the obtained developing layer coating on both sides of the PET base layer, and the coating amount is controlled at 6-12 g / m2;

[0061] S6: Dry the film obtained in S5 at 80°C to remove the dispersion liquid, thereby obtaining a low-resistance ultrasonic laser film.

[0062] Comparative Example 2 Commercially available double-sided printing ultrasonic laser film

[0063] Performance Testing

[0064] Friction resistance test: The test was conducted using a friction coefficient tester. The test conditions were coating to coating. The test results are shown in Table 1 below:

[0065] Table 1 Friction resistance test results

[0066] Average dynamic friction coefficient Average static friction coefficient Example 1 0.267 0.325 Example 2 0.378 0.437 Comparative Example 1 0.568 0.797 Comparative Example 2 0.449 0.535

[0067] Print test:

[0068] Print 100 sheets of ultrasonic laser film continuously (i.e. print 100 times) and observe the number of times the banding phenomenon occurs (banding phenomenon means that two or more sheets will come out at the same time when printing one sheet). The banding rate is the number of times the banding phenomenon occurs divided by 100.

[0069] Table 2 Automatic printing test results

[0070] Banding rate Example 1 1-2% Example 2 18% Comparative Example 1 45% Comparative Example 2 38%

[0071] Coating wear and scratch resistance test:

[0072] The ultrasonic laser film was rubbed back and forth with a steel ball with a load of 5 mm in diameter and a total of 2 kg. The number of back and forth cycles was observed to determine whether the coating would be damaged. The test results are shown in Table 3 below.

[0073] Table 3 Coating scratch resistance test results

[0074] Friction times Example 1 >200 Example 2 150-200 Comparative Example 1 150-180 Comparative Example 2 140-160

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A low-resistance ultrasonic laser film, comprising a base layer and a developing layer coated on both sides of the base layer, characterized in that: In parts by weight, the raw materials of the developing layer include:

2. A low resistance ultrasonic laser film according to claim 1, characterized in that: The hydrophobic spherical micropowder is selected from one or more of hydrophobic organic silicon elastic micropowder, polymethyl methacrylate microsphere powder, modified polytetrafluoroethylene microsphere powder, modified synthetic wax microsphere powder and modified silica spherical powder.

3. The low-resistance ultrasonic laser film according to claim 2, characterized in that: The hydrophobic spherical micropowder is selected from hydrophobic silicone elastic micropowder with a particle size of 8-12 microns and modified polymethyl methacrylate microsphere powder with a particle size of 14-18 microns.

4. The low-resistance ultrasonic laser film according to claim 1, characterized in that: The adhesive is selected from one or more of ethylene-vinyl acetate copolymer emulsion, polyurethane emulsion, carbonyl styrene butadiene latex, and acrylic emulsion.

5. The low-resistance ultrasonic laser film according to claim 1, characterized in that: The tackifier is selected from one or more of rosin resin emulsion, polyvinyl alcohol resin and polyvinyl pyrrolidone.

6. The low-resistance ultrasonic laser film according to claim 1, characterized in that: The wear-resistant agent is selected from one or more of Brazilian wax emulsion, paraffin wax emulsion, oxidized polyethylene wax powder, water-based polytetrafluoroethylene wax, and silicone emulsion.

7. The low-resistance ultrasonic laser film according to claim 6, characterized in that: The anti-wear agent is selected from oxidized polyethylene wax powder with a particle size of 4-8 microns.

8. The low-resistance ultrasonic laser film according to claim 1, characterized in that: The developer is selected from one or more of silicon dioxide, kaolin, talc, calcium carbonate, aluminum oxide, and aluminum silicate.

9. A method for preparing a low-resistance ultrasonic laser film, characterized in that: The following steps are involved: S1: Mix the wetting agent, dispersant, anti-wear agent, developer and dispersion liquid evenly, disperse at high speed for 40-80 minutes, and grind at high speed for 30-60 minutes; S2: mixing the mixed solution obtained in step S1 with the adhesive and the tackifier, and dispersing at high speed for 45-80 minutes; S3: mixing the mixed solution obtained in step S2 with the spherical micropowder, and dispersing at high speed for 45-80 minutes; S4: mixing the mixed solution obtained in step S3 with a leveling agent, dispersing at high speed for 20-40 minutes, and defoaming at low speed to obtain a developing layer coating; S5: evenly coating the obtained developing layer coating on both sides of the base layer, and controlling the coating amount to 6-12 g / m2; S6: drying the film obtained in S5 at a temperature of 60-110°C to remove the dispersion, thereby obtaining the low-resistance ultrasonic laser film as described in claims 1-8.

10. The method for preparing a low-resistance ultrasonic laser film according to claim 9, characterized in that: In the step S1, the ratio of the added mass of the dispersion liquid to the added mass of the developer is 18-22:1, and the dispersion liquid is water.